Dietary taurine effect on intestinal barrier function, colonic microbiota and metabolites in weanling piglets induced by LPS - Zhao, Dong-dong; Gai, Ye-dan; Li, Chen; Fu, Zi-zheng; Yin, De-Qi; Xie, Mingxin; Dai, Jing-yuan; Wang, Xin-xin; Li, Yan-xi; Wu, Gao-feng; Feng, Ying; Hu, Jian-min; et al. (Frontiers in Microbiology, 2023)
Diarrhea in piglets is one of the most important diseases and a significant cause of death in piglets. Preliminary studies have confirmed that taurine reduces the rate and index of diarrhea in piglets induced by LPS. However, there is still a lack of relevant information on the specific target and mechanism of action of taurine.Therefore, we investigated the effects of taurine on the growth and barrier functions of the intestine, microbiota composition, and metabolite composition of piglets induced by LPS. Eighteen male weaned piglets were randomly divided into the CON group (basal diet+standard saline injection), LPS group (basal diet+LPSintraperitoneal injection), and TAU+LPS group (basal diet+0.3% taurine+LPSintraperitoneal injection). The results show that taurine significantly increased the ADG and decreased the F/G (P < 0.05) compared with the group of CON. The group of TAU+LPS significantly improved colonic villous damage (P < 0.05). The expression of ZO-1, Occludin and Claudin-1 genes and proteins were markedly upregulated (P < 0.05). Based on 16s rRNA sequencing analysis, the relative abundance of Lactobacilluscae and Firmicutes in the colon was significantly higher in the LPS+TAU group compared to the LPS group (P < 0.05). Four metabolites were significantly higher and one metabolite was significantly lower in the TAU+LPS group compared to the LPS group (P < 0.01). The above results show that LPS disrupts intestinal microorganisms and metabolites in weaned piglets and affects intestinal barrier function. Preventive addition of taurine enhances beneficial microbiota, modulates intestinal metabolites, and strengthens the intestinal mechanical barrier. Therefore, taurine can be used as a feed additive to prevent intestinal damage by regulating intestinal microorganisms and metabolites.